Pemberdayaan Kelompok UMKM Terdampak Covid Melalui Pendampingan Ekonomi Kreatif Berbasis Teknologi - Azizah, Nuril Lutvi; Indahyanti, Uce; Latifah, Fitri Nur; Sumadyo, Sasmito Bagus (Universitas Nusantara PGRI Kediri, 2021)
Community dedication is carried out with the aim of increasing the sales turn over of cloth mask at the UMKM Tanjung which is related in the sales of goods or shops. The method used in this services activity is through partial assistance and training. Partial assistance is carried out by providing guidence and training to improve skills in making mask innovations into painting maks. Creative economy assistance is carried out by making technology-based painting masks. Masks are designed using the basic graphic design sketch application on masks, so mask sketches can be custom ordered according to the wishes of potential buyers. Painting mask can also be a differentiator from other masks that are sold in the market, thus masks have different characteristics from other masks sold in the market. The result obtained are an incrase in the selling value of painting mask and and an increase in skills in the group of UMKM Tanjung. It can be concluded that the mentoring and training activities receive positive responses from the group based on the result.